Profile of the students enrolling in the Agronomic Engineering course at a public university in the state of Tocantins, Brazil (Research, Society and Development, 2020)
This study aimed to analyze the profile of the students entering the Agronomic Engineering course, in 2019, of a public university in the state of Tocantins, as well as their motivations for choosing, in particular, that university, considering the range of other institutions possibilities, as well as their perspectives in relation to the course during and after graduated. The research was exploratory and descriptive, of a qualitative and quantitative nature and the data collection was made through a semi-structured questionnaire with open and closed questions, these being, with multiple choice option. The answers to closed questions, were analyzed based on descriptive statistics, through percentages, and the justifications for the answers to open questions through content analysis. The students entering in 2019 in the Agricultural Engineering course at the researched University were between 17 and 24 years old, with a predominance of male students, the majority of whom were from the state of Tocantins. It was not found in the study the influence of the parents' profession for the choice of the course, since most of the parents of these students work in varied activities and not linked to the agricultural / rural environment, however the choice of Agronomic Engineering by half of the students interviewed was a matter of affinity, and they are satisfied with the beginning of the course. In addition, most students mentioned that after graduating, they intend to work as Agricultural Engineers in state, with the expectation that the course will prepare them for the job market.